Halo effect moderating: impact of professional skepticism on auditor performance - Septian, Ihwan; Astika, Ida Bagus Putra (International research journal of management, IT and social sciences, 2019)
The Public Accountant profession has a role in supporting a healthy and efficient economy and increasing transparency and quality of financial information. Good auditor performance is needed to provide transparent and quality financial information to all interested parties. Good auditor performance can be carried out if an auditor is able to maintain professional skepticism and other factors in carrying out audit assignments and is not affected by factors that can reduce professional skepticism, one of which is the occurrence of a halo effect in assessing the client’s overall business risk. The research was conducted to provide empirical of the halo effect in moderating professional skepticism on the auditor performance at Public Accounting Firm (KAP) in Bali Province. The population in this research were all KAP auditors in Bali Province which registered in the Directory and published by Indonesian Institute of Certified Public Accountants (IAPI) in 2019. The sampling technique used purposive sampling with the auditor criteria who are actively working in KAP in Bali Province and has audit experience of at least one year and ever been a team leader in the audit at least once.